Norwegian folk art : the migration of a tradition - Nelson, Marion J. (Abbeville Press in association with the Museum of American Folk Art, New York, and the Norwegian Folk Museum, Oslo, 1995)
The unique charm of Norwegian folk art is commanding the attention of an ever-increasing number of museums and collectors. The rich history of these beautiful and functional objects - fanciful wood carvings, tableware and furniture with rosemaling, the snowflake patterns of Norwegian knitting, and costumes with white Hardanger embroidery - dates as far back as the Middle Ages. This volume, which illustrates nearly 250 objects spanning four centuries, reproduces some of the finest holdings of Norwegian museums, together with valuable family heirlooms brought to America and twentieth-century works created by Norwegian-American craftspeople. Many perspectives of this folk tradition are explored in the volume's ten essays, written by leading Norwegian and American scholars. This is the most comprehensive study of such varied factors as art historical traditions and influences, the social and economic background that encouraged each of these arts, Norwegian symbolism, traditional costume, and emigration to the United States and its influence on the arts. An informative and practical discussion of Norwegian folk art collections is also included. This book, the most important reference on the subject for years to come, is essential for folk art collectors, historians, and artisans, and is a fascinating cultural history for anyone of Norwegian heritage.